1999
DOI: 10.1021/ma981650e
|View full text |Cite
|
Sign up to set email alerts
|

Nonmonotonic Behavior of Sodium-Based Complex Initiators in Butadiene Polymerization

Abstract: It is frequently observed in Ziegler-Natta polymerization that the dependence of the overall polymerization rate on the catalyst/cocatalyst ratio has a more or less marked maximum (see, e.g., Porri and Giarusso 1 ). However, in lithium-initiated anionic polymerization, the addition of organometallic modifiers usually monotonically decreases the overall rate. As early as 1960, it was shown 2 that the addition of AlEt 3 or ZnEt 2 to n-BuLi gradually decreases the rate of styrene polymerization in benzene to full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…In addition, dialkylmagnesium, by itself, is not an active initiator for diene and styrene polymerization. However, in combination with organolithium, it becomes more active and initiates polymerization . Moreover, Deffieux has found that in the presence of akali metal alkoxides, isotactic-rich polystyrene is obtained using bimetallic systems, while syndiotactic-rich polystyrene is obtained using homometallic systems …”
Section: Introductionmentioning
confidence: 99%
“…In addition, dialkylmagnesium, by itself, is not an active initiator for diene and styrene polymerization. However, in combination with organolithium, it becomes more active and initiates polymerization . Moreover, Deffieux has found that in the presence of akali metal alkoxides, isotactic-rich polystyrene is obtained using bimetallic systems, while syndiotactic-rich polystyrene is obtained using homometallic systems …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, only low molecular weight polymer (M The results obtained demonstrate that multi-component anionic initiators can manifest interesting and unexpected catalytic properties which cannot be predicted by the simple metal-metal exchange mechanism. Another example of non-additive behaviour was obtained in a recent study of magnesium-sodium mixed initiator 37) .…”
Section: Resultsmentioning
confidence: 89%
“…The results obtained demonstrate that multi-component anionic initiators can manifest interesting and unexpected catalytic properties which cannot be predicted by the simple metal-metal exchange mechanism. Another example of non-additive behaviour was obtained in a recent study of magnesium-sodium mixed initiator 37) .…”
Section: Resultsmentioning
confidence: 89%